Adult spinal V2a interneurons show increased excitability and serotonin-dependent bistability - Husch, Andreas (J Neurophysiol, 2014)
In mice, most studies of the organization of the spinal central pattern generator (CPG) for locomotion, and its component neuron classes, have been performed on neonatal [postnatal day (P)2-P4] animals. While the neonatal spinal cord can generate a basic locomotor pattern, it is often argued that the CPG network is in an immature form whose detailed properties mature with postnatal development. Here, we compare intrinsic properties and serotonergic modulation of the V2a class of excitatory spinal interneurons in behaviorally mature (older than P43) mice to those in neonatal mice. Using perforated patch recordings from genetically tagged V2a interneurons, we revealed an age-dependent increase in excitability. The input resistance increased, the rheobase values decreased, and the relation between injected current and firing frequency (F/I plot) showed higher excitability in the adult neurons, with almost all neurons firing tonically during a current step. The adult action potential (AP) properties became narrower and taller, and the AP threshold hyperpolarized. While in neonates the AP afterhyperpolarization was monophasic, most adult V2a interneurons showed a biphasic afterhyperpolarization. Serotonin increased excitability and depolarized most neonatal and adult V2a interneurons. However, in ∼30% of adult V2a interneurons, serotonin additionally elicited spontaneous intrinsic membrane potential bistability, resulting in alternations between hyperpolarized and depolarized states with a dramatically decreased membrane input resistance and facilitation of evoked plateau potentials. This was never seen in younger animals. Our findings indicate a significant postnatal development of the properties of locomotor-related V2a interneurons, which could alter their interpretation of synaptic inputs in the locomotor CPG.